INDONESIAN SIDAGURI (SIDA RHOMBIFOLIA L.) AS ANTIGOUT AND INHIBITION KINETICS OF FLAVONOIDS - Syafrullah, Sarah Carolin (Majority, 2015)
Abstract Gout results from overproduction or underexcretion of uric acid and is associated with nucleic acid rich diets and the catalysis of xanthine by Xanthine Oxidase (XO) which produces uric acid.Sidaguri (Sida rhombifolia L) in Indonesian, is a traditional <a title="Find more articles at http://www.scialert.net/asci/result.php?searchin=Keywords&cat=&ascicat=ALL&Submit=Search&keyword=medicinal+plant (medicinal plant)" href="http://www.scialert.net/asci/result.php?searchin=Keywords&cat=&ascicat=ALL&Submit=Search&keyword=medicinal+plant" target="_blank">medicinal plant with potential as a remedy against gout. The earlier research reported that flavonoids crude extract from this plant could <a title="Find more articles at http://www.scialert.net/asci/result.php?searchin=Keywords&cat=&ascicat=ALL&Submit=Search&keyword=in+vitro (in vitro)" href="http://www.scialert.net/asci/result.php?searchin=Keywords&cat=&ascicat=ALL&Submit=Search&keyword=in+vitro" target="_blank">in vitro inhibit the activity of Xanthine Oxidase (XO) (xanthine: oxygen oxidoreductase EC 1.2.3.2) up to 55% and could be antigout. Keyword: flavonoids sidaguri leaf ( Sida rhombifolia L., urid acid, xanthine Oxidase Abstrak Hasil Gout dari kelebihan atau berhubungan dengan diet kaya asam nukleat dan katalisis xanthine oleh Xanthine oksidase (XO) yang menghasilkan asam urat. Sidaguri( Sida rhombifolia L) di Indonesia, merupakan tanaman obat tradisional dengan potensi sebagai obat terhadap asam urat. Penelitian sebelumnya melaporkan bahwa flavonoid ekstrak kasar dari tanaman ini bisa in vitro menghambat aktivitas Xanthine oksidase (XO) (xanthine: oksidoreduktase oksigen EC 1.2.3.2) hingga 55% dan sebagai antigout. Kata kunci: daun Sidaguri ( Sida rhombifolia L)., flavonoids, kadar asam urat, xanthine Oxidase